A case of Hemophagocytic Lymphohistiocytosis presenting as Pyrexia of Unknown Origin - Indira M; Meera Nair; Prabhalaksmi K K; Andrews M A (Mediterranean Journal of Hematology and Infectious Diseases)
Hemophagocytic lymphohistiocytosis (HLH) is a potentially fatal hyper inflammatory condition which occurs as either primary (genetic) or secondary (acquired) due to impaired or absent function of Natural Killer cells and cytotoxic cells. Common secondary causes include viral and bacterial infections, autoimmune diseases and hematological malignancies. Extensive phagocytosis of blood cells by histiocytes in bone marrow, spleen, liver and lymphnodes result in peripheral blood cytopenias, hepatosplenomegaly and lymphadenopathy. We evaluated a case of pyrexia of unknown origin and found out that he fulfilled the criteria for diagnosing hemophagocytic lymphohistiocytosis. He was started on immunochemotherapy with etoposide, cyclosporine and steroids, but he succumbed to illness within two weeks of treatment. High index of suspicion is needed to diagnose HLH and prompt treatment on diagnosis can be life saving